2008
DOI: 10.1111/j.1742-4658.2008.06355.x
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial and antifungal properties of trappin‐2 (pre‐elafin) do not depend on its protease inhibitory function

Abstract: Trappin‐2 (also known as pre‐elafin) is an endogenous inhibitor of neutrophil serine proteases and is involved in the control of excess proteolysis, especially in inflammatory events, along with the structurally related secretory leucocyte proteinase inhibitor. Secretory leucocyte proteinase inhibitor has been shown to have antibacterial and antifungal properties, whereas recent data indicate that trappin‐2 has antimicrobial activity against Pseudomonas aeruginosa and Staphylococcus aureus. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 44 publications
6
87
0
1
Order By: Relevance
“…Apart from its well known inhibitory properties, pre-elafin has been found to have broad antimicrobial properties in vitro and in vivo (14,(46)(47)(48). Although the biochemical mechanism responsible for the antimicrobial activities has not yet been elucidated, it is well known that the antimicrobial activities of pre-elafin are independent of their antiproteinase function (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from its well known inhibitory properties, pre-elafin has been found to have broad antimicrobial properties in vitro and in vivo (14,(46)(47)(48). Although the biochemical mechanism responsible for the antimicrobial activities has not yet been elucidated, it is well known that the antimicrobial activities of pre-elafin are independent of their antiproteinase function (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Although the biochemical mechanism responsible for the antimicrobial activities has not yet been elucidated, it is well known that the antimicrobial activities of pre-elafin are independent of their antiproteinase function (47)(48)(49). Recent studies have demonstrated that the N terminus of pre-elafin, responsible for most of the antimicrobial activity of the protein, adopts an a-helical conformation in the presence of a membrane mimetic, which is typical of many antimicrobial peptides (49).…”
Section: Discussionmentioning
confidence: 99%
“…It would be useful in future experiments to assess the functional impact of HVF and ECF with different concentrations of HDPs in terms of using bacterial killing assays. Moreover, there are published studies which demonstrate the antibacterial properties of both elafin and cathelicidn 42,43 .…”
Section: Authors Accepted Manuscript -24-sep-2017 Reproductionmentioning
confidence: 99%
“…This effect is mediated via impairment of both AP-1 and NF-κ B activation, via an effect on the ubiquitin-proteasome pathway [136] . Elafin also has antifungal properties [137] . Thus, like SLPI, elafin may hold therapeutic promise in the treatment of inflammation and infection in CF.…”
Section: Elafi Nmentioning
confidence: 99%